The Interest Elasticity of the Ratio of Fixed Investment to National Income as Estimated from Engineering Payout Studies - Wehle, Mark Liddell (Journal of Finance, 1964)
Mark Liddell Wehle, The Interest Elasticity of the Ratio of Fixed Investment to National Income as Estimated from Engineering Payout Studies, The Journal of Finance, Vol. 19, No. 3 (Sep., 1964), pp. 560-561